(untitled) (Journal of the College of Education for Women, 2019)
Old New York was Wharton’s term to describe this wealthy and elite class at the top ofthe developing city’s social hierarchy, a society which was utterly intent on maintaining itsown rigid stability. Even though, the roles of women in American society changed drasticallyfrom 1820’s to 1860’s due to the civil war and such a progression was due in part to therevolutionary thoughts. Women started taking their right to speak up openly and frankly andbecome more like men. The role of many women had changed from being homemaker tobeing able to provide for the family by either getting a job or start to be allowed to have avoice. They had important roles not only in helping the family, but in sharing to rebuild thenation. As a whole, they helped to clean up the process of urbanization and immigration,helping literature grow and helping change the ongoing problem of woman’s suffrage. OldNew York society to which Edith Wharton belonged did not give equality to women in legal,economic, and sexual matters. The society considered woman supremely satisfying object ofmasculine possession. Old New York imposed on its members set rules and expectations forpractically everything; manners, fashions, behaviors, and even conversations.Edith Wharton focuses on female’s characters more than men in her novels. She triesto show the sufferings of women and her society attitudes towards them, especially thedivorced women. Countess Ellen Olenska represents the major female character in The Age ofInnocence .She is considered a perfect example of women’s agony. Wharton presents EllenOlenska as the sophisticate, a woman who has been lived amid the aristocracy of Europe andhas seen the different world. Her style of dress and her manners are exotic to New York eyes,especially in her interactions with men. Everything about Olenska signaled her foreignness.She is delineated as the victim of old New York society. New York is again the center ofbizarre traditions and customs.The matter of Divorce and leaving a husband is unacceptable in New York society.Ellen wants to go home, to people who would accept her but she finds the society she isheading to be not easily accessible and also is not willing to receive anyone from the outsideworld. Ellen feels alienated and trapped when she returns to New York society. She wishes toreclaim her freedom by divorcing her husband, but she is discouraged from this actionbecause all the people around her especially her family fear unpleasant gossip.Ellen is not a mere character. She is a new heroine and representative because shestands for all female characters who try to make changes in Old New society.